Trade openness, renewable energy and environmental performance: Evidence from Africa - Ozturk, Nil Sirel (Asian Development Policy Review, 2026)
This study analyzes the determinants of economic growth and environmental performance in developing African economies using panel data from 2000 to 2021. The sample includes eight emerging African countries selected based on data availability and regional diversity. Real GDP per capita serves as a proxy for economic growth, while environmental performance is measured by the carbon intensity of GDP. Explanatory variables include trade openness, foreign direct investment inflows, renewable energy use, and urbanization. To address cross-sectional dependence and slope heterogeneity, the analysis employs second-generation panel estimators, specifically the Augmented Mean Group (AMG) and Common Correlated Effects Mean Group (CCEMG). Robustness is tested through System GMM estimations and Dumitrescu–Hurlin panel Granger causality tests. The results indicate that higher carbon intensity correlates with lower per capita income, implying that carbon-intensive production structures hinder long-term growth. Additionally, renewable energy use has a negative short-term effect on growth, reflecting adjustment costs in economies with limited institutional capacity. Overall, the findings highlight a trade-off between growth and environmental performance in Africa.